Identification of Flavoanoids From Finger Citron and Evaluation on Their Antioxidative and Antiaging Activities - Luo, Xuguang; Wang, Jin; Chen, Haiqiang; Zhou, Aimei; Song, Mingyue; Zhong, Qingping; Chen, Hanmin; Cao, Yong (Frontiers in Nutrition, 2020)
Finger citron (Citrus medica L. var. sarcodactylis Swingle) is a traditional Chinese herb and considered as a healthy food. Flavonoids are the major bioactive substances in Finger citron. In this study, the major flavonoids of finger citron (FFC) were purified with AB-8 macroporous resins and then three of them were identified as diosmetin-6-8-di-C-glucoside, hesperidin and diosmetin-6-C-glucoside, and other two were preliminarily inferred as limocitrol 3-alpha-L-arabinopyranosyl-(1->3)-galactoside and scutellarein 4'-methyl ether 7-glucoside by HPLC and UPLC-Q-TOF-MS. Further, their antioxidation and anti-aging activities were determined in vitro and in vivo. In vitro, chemical assays revealed that the purified FFC had strong antioxidative activity as demonstrated by its strong DPPH (2,2-diphenyl-1-picrylhydrazyl) and ABTS [2,2-azinobis (3-ethyl-benzothiazoline-6-sulphonic acid) diammonium salt] radical scavenging activities and ORAC (oxygen radical absorbance capacity). In vivo, the purified FFC significantly increased the mean and maximum lifespan of caenorhabditis elegans (C. elegans) by 31.26% and 26.59%, respectively, and showed no side effects on their physiological functions. Under normal and oxidative stress conditions, purified FFC reduced the accumulation of reactive oxygen species (ROS) and malondialdehyde (MDA), while increased superoxide dismutase (SOD) and catalase (CAT) enzyme activities in C. elegans. Together, we successfully identified three major substances in purified FFC of finger citron and determined the excellent anti-aging activity of FFC, which is attributed to its strong antioxidative activity and effect on homeostasis of ROS.